2021
DOI: 10.3390/ijerph18062824
|View full text |Cite
|
Sign up to set email alerts
|

Disengaging Leadership Scale (DLS): Evidence of Initial Validity

Abstract: The main goal of this study was to develop a scale for measuring Disengaging Leader-ship (DEL) behaviors and to provide preliminary evidence for the validity of this new instrument. Developing such new measures is needed given current concepts that tap into negative leadership behaviors are rarely based on a sound theoretical framework. Drawing on the core premises of Self-Determination Theory (SDT) regarding employees’ basic needs and, more specifically, building on its more recent extended framework, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Frustration of basic needs fundamentally differs from not satisfying them because it involves active thwarting rather than not stimulating and letting it run its course (Vansteenkiste and Ryan, 2013). A first study on disengaging leadership indeed showed-as expected-that it negatively relates to engaging leadership and satisfaction of basic needs, and positively to need frustration (Nikolova et al, 2021). In addition, this study found that the positive relationship between disengaging leadership and emotional exhaustion (the core component of burnout) was mediated by a frustrated need for autonomy.…”
Section: Disengaging Leadershipmentioning
confidence: 69%
See 1 more Smart Citation
“…Frustration of basic needs fundamentally differs from not satisfying them because it involves active thwarting rather than not stimulating and letting it run its course (Vansteenkiste and Ryan, 2013). A first study on disengaging leadership indeed showed-as expected-that it negatively relates to engaging leadership and satisfaction of basic needs, and positively to need frustration (Nikolova et al, 2021). In addition, this study found that the positive relationship between disengaging leadership and emotional exhaustion (the core component of burnout) was mediated by a frustrated need for autonomy.…”
Section: Disengaging Leadershipmentioning
confidence: 69%
“…Employees' perception of engaging leadership can be measured using a short self-report questionnaire consisting of three items for each of the four aspects; the Engaging Leadership Scale (ELS; see Appendix). Several studies using confirmatory factor analysis confirmed that the ELS contains four components: inspiring, facilitating, strengthening, and connecting (Rahmadani and Schaufeli, 2020;Rahmadani et al, 2020a;Nikolova et al, 2021). However, these components are so closely related that, practically speaking, it is more convenient to use the total score of the ELS.…”
Section: The Measurement Of Engaging Leadershipmentioning
confidence: 99%
“…Furthermore, while the present study provides evidence of the positive relationship between positive leadership and vigor, this is not to deny that leadership behaviors aimed at increasing followers' vigor could potentially have drawbacks for employees. Leaders who know how to increase their followers' vigor could potentially misuse these abilities and as an effect disengage and frustrate their followers (Nikolova et al, 2021). The present study did not investigate whether positive leadership can also have such negative effects on employees, for example in terms of increasing burnout.…”
Section: Limitationsmentioning
confidence: 79%
“…Consequently, this shows that leadership behaviour can either foster employee disengagement [e.g. by frustrating employees' need for autonomy, competence, connectedness or meaningfulness (Nikolova et al, 2021)], or foster employee engagement [e.g. by line manager-employee reciprocity (Cooper-Thomas and Saks, 2018;Davis and Van der Heijden, 2018;Davis, 2019), organisational justice (Saks, 2006(Saks, , 2019 and trust (Macey and Schneider, 2008)].…”
Section: External Contextmentioning
confidence: 99%
“…Consequently, this shows that leadership behaviour can either foster employee disengagement [e.g. by frustrating employees' need for autonomy, competence, connectedness or meaningfulness (Nikolova et al. , 2021)], or foster employee engagement [e.g.…”
Section: The Dynamic Employee Engagement Frameworkmentioning
confidence: 99%